Osmotin an antifungal cytotoxic from Solanum tuberosum: New insights into structural and antifungal properties - Tiwari, Jagesh Kumar; Singh, Ritu; Rawat, Shashi (Potato Journal, 2017)
Pathogenesis related (PR) proteins are considered as the major sources in plant’s defense against pathogens as well as other biotic and abiotic stresses. We present here the 3-D structure of potato (Solanum tuberosum L.) osmotin-like protein (StOLP) based on homology modelling using structure validation programs namely PROCHECK, PROSA, VERIFY3D and WHATIF. The model revealed that StOLP protein shared 16 conserved Cys, which formed eight disulfide bonds. The 3-D structure of StOLP showed three characteristic domains showing similarity fold with the thaumatin. Domain 1 consisted of a flattened 11-β strands (six antiparallel β strands present in the front end and other five antiparallel β strands are located at the back) which together constituted the β-sandwich. Domain II consisted of an α-helix and three shorter domains which formed loops exposed on the molecular surface of the protein. Together with domain I, domain II formed a large cleft region on the protein surface. Domain III consisted of a small loop of 32 residues which formed a long loop consisting of two β sheets. This modelling effort provided structural predictions of the catalytic domain of StOLP that are being verified via experimental techniques. These results provided evidence of antifungal activity for a S. tuberosum osmotin-like protein against the fungus Phytophthora Infestans causes late blight disease to potato. Homology modelling, osmotin-like proteins, antifungal, ProCheck validation, 3D structure, alignment